2022
DOI: 10.1007/s10198-021-01422-w
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness of screening smokers and ex-smokers for lung cancer in the Netherlands in different age groups

Abstract: Objective We aimed to assess the cost-effectiveness of screening smokers and ex-smokers for lung cancer in the Netherlands. Methods A Markov model was used to evaluate the health effects and costs of lung cancer screening from the healthcare perspective. The effects and costs of ten screening scenarios with different start and stop ages of screening were examined across a lifetime horizon in a cohort of 100,000 smokers and ex- smokers 50 years and older. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…In total, 16 (48%) studies present ACERs rather than ICERs [ 25 , 30 , 39 – 52 ]. An additional 6 (18%) studies estimate ICERs of annual screening without assessment against biennial comparators [ 28 , 32 36 ]. A further 2 (6%) studies are classified as reporting ICERs as they have assessed one-time screening per lifetime [ 30 , 31 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In total, 16 (48%) studies present ACERs rather than ICERs [ 25 , 30 , 39 – 52 ]. An additional 6 (18%) studies estimate ICERs of annual screening without assessment against biennial comparators [ 28 , 32 36 ]. A further 2 (6%) studies are classified as reporting ICERs as they have assessed one-time screening per lifetime [ 30 , 31 ].…”
Section: Resultsmentioning
confidence: 99%
“…As the latter is more comprehensively reported we excluded the former. Three additional studies were found from citation tracking [27][28][29]. Ultimately, 33 articles were accepted for critical appraisal.…”
Section: Overviewmentioning
confidence: 99%
See 2 more Smart Citations
“…The implementation of population-based lung cancer screening of high-risk individuals could decrease the percentage of inoperable patients who are diagnosed with stage III (21%) and IV (49%) lung cancer. A Dutch-initiated randomized lung cancer screening trial, known as the NELSON trial, has recently proven to result in a decrease in lung cancer mortality by 26% and to be cost-effective in the Netherlands (67)(68)(69). Although lung cancer screening programs are currently implemented in several European centers (70), screening for lung cancer with low-dose computed tomography is presently not yet implemented in the Netherlands because of legal restrictions (67).…”
Section: Lung Cancer Screening Of High-risk Individualsmentioning
confidence: 99%